Digital Technology on Financial Inclusion and Economic Justice in Indonesia - Chotrianda, Nadhia Fortuna; Setiawan, Doni; Mawardi, Wisnu (LifeSciFi, 2024)
The digital revolution in financial services has significantly changed the landscape of financial inclusion. Financial inclusion and economic justice remain a major challenge for the poor and vulnerable, especially in developing countries like Indonesia. Digital technology is developing as a promising alternative for increasing access to services of formal financial, reducing economic inequalities, and improving people’s well-being. This study investigates the function of digital technologies in fostering financial inclusion and economic justice across the social strata in Indonesia. The findings show that digital technology has enhanced access financial services, reduced inequality and opened new economic opportunities for communities. However, there are challenges in ensuring equal access to digital financial services, including literacy barriers, infrastructure gaps, and security concerns. By evaluating government initiative and private sector engagement in promoting financial inclusion, this study highlights the critical role of digital tools in advancing economic justice. The research contributes by providing policy recommendations to improve access to digital technologies, expand financial inclusion, and support more equitable and sustainable economic growth.